Validation of C-Reactive Protein and CURB-65 in The FirstHospital Admission Community Acquired Pneumonia Patient asA Predictor 30 Days Mortality - Buharman, Borries Foresto; Pitoyo, Ceva Wicaksono; Singh, Gurmeet; Koesnoe, Sukamto (UI Scholars Hub, 2018)
Child Turcotte Pugh Score, diastolic dysfunction, liver cirrhosis, liver dysfunction